Acurácia e precisão na formulação não linear de ração para frangos de corte: avanço e otimização de resultados - Gonçalves, Camila Angelica [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The poultry industry has sought to optimize animal production. For this reason, the mathematical modeling is an essential tool to achieve greater control and production planning, appropriate to the different feeding conditions, market and economic interests. This study aimed to obtain mathematical models capable of predicting the responses of broiler performance due to changes in levels of energy density, according to the phase and sex, as base to a system of nonlinear feed formulation. Therefore, two experiments were conducted simultaneously, for 240 broiler females and 240 males. The birds were distributed in a completely randomized design with six energy levels (2,800; 2,900; 3,000; 3,100; 3,200 and 3,300 kcal ME/kg, maintaining the relationship between energy and other nutrients) and four replicates of ten birds, allocated to floor pens. Data on body weight, feed intake, energy consumption, feed conversion, carcass weight and abdominal fat were analyzed by response surface methodology. Feed intake and body weight were used to determine rates of gain that maximize economic return, according to the energy density, the market prices of ingredients and kilogram of broilers. It was concluded that the concept of nonlinear formulation seems more appropriate to meet the concept of precision nutrition for broilers, since the requirements of all nutrients are automatically adjusted by the mathematical model related to energy content estimated, according to the nutritional recommendations for different ages and stages of broilers, according to the program PPFR
Keywords: Frango de corte; Desempenho; Excel for Windows (Programa de computador); Metadados; Precisão da medição dimensional; Produção animal; Nutrição animal; Balanced ration